Cuius Regio? Ideological and Territorial Cohesion of the Historical Region of Silesia (c. 1000-2000) vol. 1. The Long Formation of the Region Silesia (c. 1000-1526) - Wiszewski, Przemysław; Goliński, Mateusz (Publishing House eBooki.com.pl, 2013)
This collection of articles represents the output of the first stage of research on the history of the region of Silesia, conducted under the patronage of the European Science Foundation as part of the project 'Cuius regio. An analysis of the cohesive and disruptive forces determining the attachment and commitment of (groups of) persons to and cohesion within regions'. Silesia, one of the regions analyzed in the project, is an example of a borderland territory whose historical development was substantially influenced by various cultural traditions. The primary goal of the research on the Silesian history was to determine the factors that led to disintegration and subsequent re-creation of the region, for there are arguments indicating that the history of the local community has been – and continues to be - the product of a dynamic process whose course was not determined solely by the factor of its constant existence within the limits demarcated within the 16th-century Kingdom of Bohemia.
Keywords: social cohesion; Silesia; regional history